Accepting the inevitable: A mixed method approach with assessment and perceptions of well-being in very old persons within the northern Sweden Silver-MONICA study. (January 2021) - D. Almevall, Albin; Zingmark, Karin; Nordmark, Sofi; Forslund, Ann-Sofie; Niklasson, Johan
Highlights: Morale levels correlated with feeling lonely, self-assessed health, physical function and capacity, living in own house, age and depression. Perceptions of aspects important to well-being were described as social context, health, physical activity, home, engagement and freedom. Acceptance was found to be a key factor for perceived well-being in very old persons, and the acceptance could be reoriented or resigned. A mixed method approach gives insights into the comparison between assessment and perceptions of well-being. This study offers a possible new approach to using assessment scales in clinical praxis. Abstract: Background: As the group of very old persons will form an increasing part of society, the study of how well-being is described and affected by specific factors will be of importance to meet the future needs of these persons. The aim of the study was to increase knowledge of well-being in very old persons by combining assessments and perceptions using the Philadelphia Geriatric Morale Scale (PGCMS). Method: In a mixed method, convergent parallel design, 52 persons 80 years or older were assessed and interviewed using the PGCMS to combine assessment of morale and descriptions of perceptions of well-being using a mixed method approach. Results: Quantitative and qualitative results converged in four areas: not feeling lonely and being included, rating and perceiving health as good, high physical function/ability and being physically active, living in own house and feeling at home. Areas perceived as important to well-being captured only in qualitative analysis were having freedom and engagement. An example of insights not achievable from the quantitative or qualitative analysis alone was that individuals with high morale expressed anxiety about losing their health due to potential ageing-related threats and that individuals with low morale struggled with acceptance. Acceptance was the key strategy for handling adverse consequences of ageing in all described areas. Conclusion: When using standardized assessment scales in clinical practice, it could be useful to combine quantitative and qualitative data. Acceptance was key for well-being; however, acceptance could be resigned or reorienting in nature.